Inductance energy storage pulse power source utilizing superconductive pulse transformer - LIU SHUCUN; WAN LONG; ZHANG XIAOTONG; LI HAITAO; LIU NA; LI ZHENMEI (2016)
The invention relates to an inductance energy storage pulse power source utilizing a superconductive pulse transformer and belongs to the technical field of pulse power. The inductance energy storage pulse power source is characterized by comprising the superconductive pulse transformer, a primary side of the superconductive pulse transformer is provided with a primary power source, an output end of the primary power source is separately connected with a conversion branch, a freewheeling branch and two ends of a superconductive pulse transformer primary winding through a controllable switch S1, an energy recuperation branch is connected between the conversion branch and the primary power source, for a secondary side of the superconductive pulse transformer, one end of a secondary side winding is connected with one end of a load control branch, the other end of the secondary side winding is separately connected with at least one set of superconductive energy storage inductance charging branches and one end of